131 Rapid and sustained increase in #FOAMed based education during COVID-19 on the St Emlyn's blog and podcast. Issue 12 (23rd November 2020) - Carley, Simon; Jafar, Anisa; Reynard, Charlie; Beardsell, Iain; Horner, Dan; Liebig, Ashley Voss; Body, Richard
Abstract : Aims/Objectives/Background: COVID 19 has resulted in a rapid and unplanned change in the way that education is delivered and consumed. The St Emlyn's team published a range of webinars, blogs, podcasts and critical appraisal articles specifically focused on COVID-19 during the pandemic. Some webinar content was published in conjunction with the Royal College of Emergency Medicine and the University of Manchester. We reviewed how engagement with the free and open access medical education (FOAMed) St Emlyn's blog and podcast changed as a result of the pandemic Methods/Design: We compared the number of visits for the last 12 months against the previous 12 months. We obtained data from Wordpress and Podbean platforms for the blog and podcast respectively. We did not add data from other social media platforms such as Twitter and Facebook. Differences are expressed as a ratio to indicate an increase or decrease in the number of engagements from the previous year. Results/Conclusions: The data shows similar levels of between year activity from July 2018 through to February 2019. It then shows a rapid and profound increase in activity from March 2019, coinciding with the rapid spread of the pandemic in Europe and an early blog/podcast with colleagues from Northern Italy. Since then activity has fallen but still remains roughly 1.5 times higher than in previous years. Combined visits to the blog and podcast peaked at 162, 019 engagements, representing a near 6.9 fold increase in podcast engagement and a 2.7 increase in blog activity during May 2019. The COVID-19 pandemic resulted in a rapid and sustained engagement with the St Emlyn's platform. The reasons for this are unclear from the data presented here, but we believe reflect the superior agility of modern educational tools such as blogs and podcasts to share and disseminate information as compared to traditional academic publishing methods.